2014
DOI: 10.1186/s40604-014-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Smart cities: the state-of-the-art and governance challenge

Abstract: Reflecting on the governance of smart cities, the state-of-the-art this paper advances offers a critique of recent city ranking and future Internet accounts of their development. Armed with these critical insights, it goes on to explain smart cities in terms of the social networks, cultural attributes and environmental capacities, vis-a-vis, vital ecologies of the intellectual capital, wealth creation and standards of participatory governance regulating their development. The Triple Helix model which the paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 20 publications
(17 reference statements)
4
57
0
7
Order By: Relevance
“…Such a significance of service industry sectors facilitated by ICT infrastructure appears in accordance with previous studies, which empirically showed that a wide spectrum of ICT applications led to the accumulation of intellectual capital, ultimately resulting in wealth creation by means of interconnecting human and social capital via activated knowledge networks [11,12,30,31]. For instance, this study found the high induction coefficients of employment of the smart city industry in service industry sectors, including Professional, scientific and technical activities and Administrative and support service activities, supporting the idea that human and social capital can be leveraged by ICT-based public administration and education, thus improving the competitiveness of a smart city [11].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Such a significance of service industry sectors facilitated by ICT infrastructure appears in accordance with previous studies, which empirically showed that a wide spectrum of ICT applications led to the accumulation of intellectual capital, ultimately resulting in wealth creation by means of interconnecting human and social capital via activated knowledge networks [11,12,30,31]. For instance, this study found the high induction coefficients of employment of the smart city industry in service industry sectors, including Professional, scientific and technical activities and Administrative and support service activities, supporting the idea that human and social capital can be leveraged by ICT-based public administration and education, thus improving the competitiveness of a smart city [11].…”
Section: Discussionsupporting
confidence: 84%
“…The relatively high contribution of the smart city industry to the induction coefficients of employment in Professional, scientific and technical activities and Administrative and support service activities sectors supports the idea that human and social capital can be leveraged by public administration and education based on ICT, improving in turn the competitiveness of a city [12]. This also appears to agree well with the findings of the previous studies, which empirically showed that various ICT applications in smart cities ultimately led to the build-up of intellectual capital or the creation of wealth by means of the interconnection of human and social capital via activated knowledge networks [11,12,30,31].…”
Section: Effect Of the Smart City Industry On Other Industriessupporting
confidence: 85%
See 1 more Smart Citation
“…The 'Helices' model tends to emerge as a theoretical perspective and organizational framework for cities 'smart oriented' and strategically driving innovation in providing services, building material, and immaterial infrastructures in order to support growth in urban areas. Sustainable development of cities seems to rely on following both the 'smart cities approach' and the 'Helices' model as drivers for sustaining innovation (Afonso, Monteiro, & Thompson, 2010;Carayannis, Barth, & Campbell, 2012;Danson & Todeva, 2013;Deakin, 2014;Etzcowitz & Leydensdorff, 1998, 2000Etzcowitz, 2003;Etzkowitz & Zhou, 2006;Leydesdorff & Deakin, 2011;Todeva, 2013).…”
Section: Mauro Romanellimentioning
confidence: 99%
“…This perspective tends to emphasize the role of cities as 'smart' and incubators of intellectual capital, enabling the creation of wealth and regulators of standards by involving universities, industry, government and civil society as one of the main key actors in promoting the development and performance of cities being smart (Lombardi, Giordano, Farouh, & Yousef, 2011). Cities following the 'Triple Helix' model tend to become smart when the ICTs of future Internet developments successfully embed the networks society needs for them sustaining intellectual capital and wealth, developing both the environmental capacity, the ecology and vitality of those spaces enriched by direct democracy and participatory governance adding value (Deakin, 2014). 5 (2017) no.1, pp.119-135; www.managementdynamics.ro Building a 'Smart' and 'European' design for driving sustainable cities Cities proceeding towards sustainability should adopt and implement a design relying on following the 'smart cities approach' as paradigm leading cities to the future.…”
Section: Mauro Romanellimentioning
confidence: 99%